ILLUSTRASI SUASANA COFFEE SHOP DENGAN MEDIA WATERCOLOUR - Nurul Azizah; Syafwan Syafwan (Serupa The Journal of Art Education, 2020)
The purpose of this final work is to visualize the illustration of the coffee shop atmosphere. The  method of creating works of art uses five stages of work, namely, the preparation stage, the elaboration stage, the synthetic stage, the concept realization stage, and the completion stage, and finally holding a painting exhibition. The techniques used are arsi and aquarelle techniques. There are 10 works created, namely, 1. Welcome to Coffee Shop, 2. Coffee on One Table, 3  Study Art, Coffee  Friends, 8. Bullshit Roasting, 9. From Heart to Heart, 10. Little Memories.Kata Kunci : Coffee Shop, Illustrasi